The role of the slab pull force in the late Oligocene to early Miocene extension in the Southern Central Andes (27°-46°S): Insights from numerical modeling - Fennell, Lucas Martín (2018)
Although extensional deformation plays a significant part of Andean history, the causes behind its driving mechanisms and its impact throughout the geological record remain controversial. Through the aid of numerical modeling of subduction zone dynamics, we were able to reproduce a brief period of intra-arc basin formation that affected the Southern Central Andes (27°-46°S) during late Oligocene and early Miocene times. The results of the model show that, after a period of slow subduction (6–8 cm/yr), the oceanic plate approaches the mantle transition zone at ca. 23 Ma, triggering the slab pull force. The addition of this slab pull force generates a progressive increase in convergence velocity (reaching ∼20 cm/yr) and the retreat of the trench hinge away from the upper plate, resulting in the steepening of the slab. Effects observed in the upper plate are the formation of a basin located 200–300 km east of the trench and an asthenospheric influx beneath an 800 km wide zone east of the oceanic and continental plate's boundary. A series of parameters extracted from our model, such as the basin depth and the stretching factor, indicate that crustal stretching, basin formation, convergence velocity and asthenospheric influx would have reached their climax approximately at 20 Ma. These results are in good correlation with the convergence rate obtained through plate reconstructions and the geological record along the Southern Central Andes, where a series of extensional intra-arc basins were created and mantle derived magmatic processes affected a wide area ranging between the present fore-arc and retroarc areas during late Oligocene to early Miocene times. However, differences in extension magnitude, magma composition and basin fill depositional environment are observed, indicating that the impact of the slab pull force was stronger towards the southern basins. Possible causes that could explain these differences are variations in crustal thickness before the influence of the slab pull force and the effect of toroidal mantle flow near the southern lateral slab edge. This would indicate that although the main parameter controlling tectonic regime is the absolute motion of the overriding plate, the slab pull force may leave its imprint along the evolution of subduction-type orogens such as the Andes.